Réponses

  • Omnes
  • Modérateur confirmé
2014-03-09T23:01:26+01:00
Salut,

(2- \sqrt{3})^{2} - ( \sqrt{5} -1)^{2} \\
2^{2} - 2*2* \sqrt{3} +  \sqrt{3}^{2} - ( \sqrt{5} ^{2} - 2 * 1 *  \sqrt{5} +1^{2}) \\
4 - 4\sqrt{3}  + 3 - (5 -2 \sqrt{5} +1) \\
7 - 4\sqrt{3} - 5 + 2 \sqrt{5} - 1 \\
1 - 4\sqrt{3} + 2 \sqrt{5}

Bonne soirée !
Merci, et celle-ci? (4 - 2 [3])^ svp
4² - 2 * 4 * 2V2 + (2V3)² = 16 - 16V3 + 4*3 = 16 - 16V3 + 12 = 28 - 16V3
bonjour Omnes j'aurai besoin de ton aide si tu peux mon pseudo c'est katchou
2014-03-09T23:02:48+01:00
Bonsoir,

(2-\sqrt{3})^2 - (\sqrt{5}-1)^2\\\\=(2^2-2\times2\times\sqrt{3}+(\sqrt{3})^2) -((\sqrt{5})^2-2\times\sqrt{5}\ti+1^2)\\\\=(4-4\sqrt{3}+3) -(5-2\sqrt{5}+1)\\\\=(7-4\sqrt{3}) -(6-2\sqrt{5})\\\\=7-4\sqrt{3} -6+2\sqrt{5}\\\\=1-4\sqrt{3} +2\sqrt{5}
Merci, et cellle ci? 3 [5] x 7 [15] x 6 [21] svvp
3V5 * 7V15 * 6V21 = 126V(5*15*21) = 126V1575 = 126 * 15V7 = 1890V7